(untitled) (Italian Journal of Public Health, 2008)
Background: Health system performance is a multi-dimensional concept related to the achievement of several objectives such as effectiveness, efficiency and equity. The aim of this study is to investigate the relationship between models of health care systems (Beveridge, Bismarck and voluntary health insurance) and performance frameworks available in the scientific literature. Methods: An extensive literature search in several electronic databases was carried out. According to a preliminary classification of performance domains and dimensions, we analysed, among the selected articles, the relationship between domains/dimensions and the three main models of health care systems.Results: 12.6% of the children were obese and 26.3% overweight, with the percentage of obesity nearly double in those who do not practice organized sports activities at least once a week, in those who don’t have breakfast in the morning and in those who don’t spend their free time in movement games. From a multiple logistic regression it results that the risk of being obese is twice and three times higher for the children living respectively in medium and small towns than for the ones living in large towns. Results: From 540 references found, 17 papers were considered relevant for the purposes of this research. A total of 39 frameworks were identified: 41% referred to the “Beveridge model, 10% to the “Bismarck model”, and 23% to the “Voluntary health insurance” model and 26% to “Umbrella organizations” (e.g. OECD). Domains of effectiveness and responsiveness were covered by all of the frameworks while fewer covered equity and efficiency. The most frequent dimensions in all the models were effectiveness and technical efficiency, but relevant differences exist among the healthcare system models about dimensions of performance considered. Conclusions: Although the need of evaluate health care systems performance is recognized, there is not agreement on what concepts and dimensions of performance should be measured. Our study underlines an interesting link between the domains/dimensions of performance assessment and models of health care systems